Clinical and genetic characterization of patients with late onset Wilson’s disease - Wenming Yang; Yue Yang; Han Wang; Jiuxiang Wang; Shijie Zhang (npj Genomic Medicine)
Abstract Wilson’s disease (WD) typically manifests in children and young adults, with little knowledge of its late-onset forms. In this study, we performed a retrospective cohort study of 105 WD patients (99 index cases, 6 siblings) with an onset age ≥35 years. We compared 99 index late-onset patients with 1237 early-onset patients and analyzed the ATP7B variant penetrance referring to the Genome Aggregation Database (gnomAD). Sixty-two ATP7B variants were identified in the late-onset patients, among which A874V, V1106I, R919G, and T935M were correlated with late presentation of WD. Regarding gnomAD, V1106I and T935M exhibited significantly low penetrance, and there is a lack of patients carrying a genotype of V1106I/V1106I, R919G/R919G, T935M/T935M, V1106I/T935M, V1106I/R919G, or T935M/R919G. Our data revealed that patients carrying a combination of two late-onset variants may be overlooked due to atypical or lack of WD symptoms, which may provide valuable insights into the genetic basis and diagnosis of WD.